UPAYA MENJAGA SANAD KEILMUAN DENGAN ULAMA’ ASWAJA MELALUI KEGIATAN “MBALAH ASWAJA” DI UNIVERSITAS ISLAM MALANG - Mohammad Hakim, Dian; Ainun Nadziroh, Alvin; Nisa’ul Hamidah, Farhatun; Urfi Nazilla , Zumrotul (An Nahdhoh Jurnal Kajian Islam Aswaja, 2024)
The phenomenon of lack of care in choosing ustaz or clerics to study religion is a serious concern in Muslim society today. This article highlights the tendency of society to be more careful in world affairs than in choosing religious teachers. In the midst of the rise of fake ustaz who spread liberal ideas without in-depth research, the importance of choosing a ustaz with the right criteria becomes very relevant. With the historical example of Imam Bukhari who had many teachers, this article underlines the importance of guidance and authority in understanding religious teachings. For ordinary people who do not have the ability to research religious teachings, having a teacher who can guide them is the key to avoiding error and confusion in understanding religion.